2015
DOI: 10.1148/radiol.14140251
|View full text |Cite
|
Sign up to set email alerts
|

Establishing the Lysine-rich Protein CEST Reporter Gene as a CEST MR Imaging Detector for Oncolytic Virotherapy

Abstract: Purpose:To (a) evaluate whether the lysine-rich protein (LRP) magnetic resonance (MR) imaging reporter gene can be engineered into G47D, a herpes simplex-derived oncolytic virus that is currently being tested in clinical trials, without disrupting its therapeutic effectiveness and (b) establish the ability of chemical exchange saturation transfer (CEST) MR imaging to demonstrate G47D-LRP. Materials and Methods:The institutional subcommittee for research animal care approved all in vivo procedures. Oncolytic he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
76
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 70 publications
(78 citation statements)
references
References 26 publications
2
76
0
Order By: Relevance
“…This has been demonstrated for the LRP CEST reporter gene; following the initial study where it was shown that the contrast generated from LRP can be differentiated from controls, its practicality has been repeatedly demonstrated in live rodents and enabled collection of high temporal and spatial resolution images (76,77). Farrar and colleagues have confirmed that LRP can be visualized in live rats after delivery of an oncolytic virus, thus serving as a marker for treatment efficacy (78) (Fig. 4).…”
Section: Cest Reporter Genes For Cellular Imagingmentioning
confidence: 91%
“…This has been demonstrated for the LRP CEST reporter gene; following the initial study where it was shown that the contrast generated from LRP can be differentiated from controls, its practicality has been repeatedly demonstrated in live rodents and enabled collection of high temporal and spatial resolution images (76,77). Farrar and colleagues have confirmed that LRP can be visualized in live rats after delivery of an oncolytic virus, thus serving as a marker for treatment efficacy (78) (Fig. 4).…”
Section: Cest Reporter Genes For Cellular Imagingmentioning
confidence: 91%
“…This “catalytic” contrast scheme is called chemical exchange saturation transfer, or CEST. Proteins detectable with this method include a synthetic lysine-rich protein 29 and human protamine 30 .…”
Section: Biomolecular Tools For Magnetic Resonance Imagingmentioning
confidence: 99%
“…However, in in vivo applications, biomolecular CEST agents must also overcome background CEST contrast from endogenous proteins, making their detection at such low concentrations more difficult. Despite this limitation, protein-based CEST reporters have been used in several in vivo applications, and innovative pulse sequences and processing schemes have been developed to help maximize reporter-specific contrast [38–40]. …”
Section: Established Mechanisms Of Biomolecular Mri: T1 T2 Cestmentioning
confidence: 99%